Mismatch Repair Deficiency and Microsatellite Instability in Triple-Negative Breast Cancer: A Retrospective Study of 440 Patients - Ren, Xin-yu; Song, Yu; Wang, Jing; Chen, Long-yun; Pang, Jun-yi; Zhou, Liang-rui; Shen, Song-jie; Cao, Xi; Wang, Yu-xin; Shao, Miao-miao; Liang, Zhi-yong; Sun, Qiang; et al. (Frontiers in Oncology, 2021)
Purpose: To investigate the status of mismatch repair (MMR) and microsatellite instability (MSI) in triple-negative breast cancer (TNBC) and to examine correlations between MMR/MSI status and clinicopathological parameters. Methods: We retrospectively collected tissue samples from 440 patients with TNBC and constructed tissue microarrays. Protein expression of MLH1, MSH2, MSH6, and PMS2 was detected by immunohistochemistry (IHC). We also analyzed 195 patient samples using MSI polymerase chain reaction (PCR) testing. Correlations between MSI status and clinicopathological parameters and prognosis were analyzed. Results: The median age of the cohort was 49 years (range: 24–90 years) with a median follow-up period of 68 months (range: 1–170 months). All samples were positive for MLH1, MSH2, MSH6, and PMS2, except for one sample identified as MMR-deficient (dMMR) by IHC, with loss of MSH2 and intact MSH6 expression. MSI PCR revealed no cases with high-frequency MSI (MSI-H), whereas 14 (7.2%) and 181 (92.8%) samples demonstrated low-frequency MSI and microsatellite stability, respectively. The dMMR sample harbored low-frequency instability, as revealed by MSI PCR, and a possible EPCAM deletion in the tumor, as observed from next-generation sequencing. No correlations were detected between MMR or MSI status and clinicopathological parameters, programmed cell death 1 (PD-1)/programmed cell death ligand 1 (PD-L1) expression, or survival. Conclusions: The incidence of dMMR/MSI-H is extremely low in TNBC, and rare discordant MSI PCR/MMR IHC results may be encountered. Moreover, MMR/MSI status may be of limited prognostic value. Further studies are warranted to explore other predictive immunotherapy biomarkers for TNBC.